Improved quantitative myocardial T2 mapping: impact of the fitting model - Akçakaya, Mehmet; Weingärtner, Sebastian (Magnetic resonance in medicine, 2014)
Purpose: To develop an improved T2 prepared (T2prep) balanced steady-state free-precession (bSSFP) sequence and signal relaxation curve fitting method for myocardial T2 mapping. Methods: Myocardial T2 mapping is commonly performed by acquisition of multiple T2prep bSSFP images and estimating the voxel-wise T2 values using a two-parameter fit for relaxation. However, a two-parameter fit model does not take into account the effect of imaging pulses in a bSSFP sequence or other imperfections in T2prep RF pulses, which may decrease the robustness of T2 mapping. Therefore, we propose a novel T2 mapping sequence that incorporates an additional image acquired with saturation preparation, simulating a very long T2prep echo time. This enables the robust estimation of T2 maps using a 3-parameter fit model, which captures the effect of imaging pulses and other imperfections. Phantom imaging is performed to compare the T2 maps generated using the proposed 3-parameter model with the conventional two-parameter model, as well as a spin echo reference. In vivo imaging is performed on eight healthy subjects to compare the different fitting models. Results: Phantom and in vivo data show that the T2 values generated by the proposed 3-parameter model fitting do not change with different choices of the T2prep echo times, and are not statistically different than the reference values for the phantom (P = 0.10 with three T2prep echoes). The two-parameter model exhibits dependence on the choice of T2prep echo times and are significantly different than the reference values (P = 0.01 with three T2prep echoes). Conclusion: The proposed imaging sequence in combination with a three-parameter model allows accurate measurement of myocardial T2 values, which is independent of number and duration of T2prep echo times.